Extension disorders of fingers with congenital anomalies of the flexor digitorum profundus: a case report - Wang, Benbiao; Luo, Deguo; Zhuo, Naiqiang; Xu, Yulin; Ge, Jianhua (Frontiers in Surgery, 2025)
IntroductionAn aberrant origin of the deep flexor muscle causing congenital flexion deformity of the middle, ring, and little fingers is relatively atypical, and its etiology remains unclear. Previous reports indicate that surgeons have employed a muscle-sliding procedure of the flexor muscles to treat the condition. However, postoperative loss of motion was observed. In our patient, we enhanced the original surgical method by incorporating intramuscular extension of the superficial digital flexor muscle, along with close follow-up and guidance on functional exercises, leading to improved outcomes for the patient. These results may serve as a valuable reference for clinical practice.Main symptoms and important clinical findingsThe physical examination demonstrated the three affected fingers showed flexion deformity upon wrist extension. The three fingers could be actively extended when the wrist was flexed. During the examination, the patient experienced no pain, and the thumb and index fingers exhibited normal motion. The diagnostic assessment was completed with x-ray, 3D CT, and MRI of the forearm.Therapeutic interventions and outcomesThe patient underwent surgery: the bony process was excised, followed by severing of the tendinous band, the contracted tissues at the deep flexor tendon origins were further released toward the radial side. Muscle sliding was followed by the resection of the hyperintense tendinous portion of the superficial flexor. Postoperatively, the wrist joint was externally fixed using plaster at 30° dorsiflexion, and the fingers were extended for 3 weeks, along with close follow-up and guidance on functional exercises, Finally, the affected side is functionally equivalent to the unaffected side.ConclusionThe incidence of this condition is relatively low, but diagnosis is relatively straightforward. It requires differentiation from other finger deformities. Based on the degree of contracture, the patient's age, and findings during the intraoperative examination, an appropriate surgical approach should be selected. Combined with close follow-up and functional exercise guidance, favorable treatment outcomes can be achieved.